Patterns of Factors in the National Institute on Aging Health Disparities Research Framework Domains and Mild Cognitive Impairment Risk - Maria Vassilaki, MD, PhD; Jeremiah A. Aakre, MPH; Timothy G. Lesnick, MS; Walter K. Kremers, PhD; Jonathan Graff-Radford, MD; David S. Knopman, MD; Thomas H. Mosley, PhD; B. Gwen Windham, MD, MHS; Michael E. Griswold, PhD; Yonas E. Geda, MD, MSc; Val J. Lowe, MD; Clifford R. Jack, Jr., MD; et al. (AJPM Focus)
Introduction: Alzheimer's disease and related dementias are public health and social care challenges. This study used the National Institute on Aging Health Disparities Research Framework to organize potential cognitive impairment risk factors. It aimed to examine patterns of environmental, sociocultural, behavioral, and biological factors and identify key components that predict mild cognitive impairment risk. Methods: This study comprised 2,812 participants from the Mayo Clinic Study of Aging who were cognitively unimpaired at baseline (aged ≥50 years, mean age [SD]=68.9 [9.7] years, 50.4% female). Analyses utilized a 2-stage approach using factor and principal component analyses to group factors from multiple National Institute on Aging Health Disparities Research Framework domains and identify components that predict cognitive impairment risk. Using a cohort study design, the resulting composite scores were considered as covariates for incident mild cognitive impairment analysis using Cox proportional hazards models. Results: Three principal components explained 40.30% of the variance and were differentially associated with mild cognitive impairment risk. One component (Principal Component 2), which included factors from all 4 domains of the National Institute on Aging Health Disparities Research Framework (including social, group, and playing game activities [sociocultural domain]; exercise and physical activity [behavioral domain]; education/occupation [environmental domain]; and absence of cardiometabolic risk factors/health self-rating [biological domain]), was associated with lower mild cognitive impairment risk (hazard ratio=0.80, 95% CI=0.73, 0.89). The other 2 principal components, also including factors from multiple framework domains, were associated with increased mild cognitive impairment risk. Conclusions: Derived principal components included factors from multiple framework domains, supporting the multietiology pathways leading to cognitive impairment. These principal components were differentially associated with mild cognitive impairment risk. Identifying key factors from multiple National Institute on Aging Health Disparities Research Framework domains associated with cognitive impairment risk has implications for effectively targeting interventions at multiple levels (e.g., medical, societal, policy) to avert or delay cognitive impairment risk.